EFEKTIVITAS KOMBINASI PEMBELAJARAN DARING DAN TATAP MUKA PADA MATA KULIAH STATISTIKA DI MASA PANDEMI - Stefany Margareta Martono; Vina N Van Harling (SOSCIED, 2021)
Currently, all activities in various fields are mandatory work from home, including in the field of education. Saint Paul Polythecnic Sorong passes 1 academic year with full online learning, then in the even semester 2020/2021 academic year, implementing learning with a combination of online and face- to face learning activities. Researchers conducted research with the aim of knowing the effectiveness of the combination of online and face to face learning in statistics courses during the pandemic. To test the effectiveness of this learning combination, the researcher used a research instrument in the form of a questionnaire. Based on the data that has been obtained, the result of the questionnaire stated that 10% stated that it was not effective, 4% said it was less effective, 3% said was quite effective, 4% said it was effective and 79% stated that the combination of online and face – to - face learning was very effective in statistics course in Indonesia pandemic period. This is evidenced by the statistical hypothesis in this study, namely H_a:ρ>75% (The combination of online and face -to - face learning in statistics courses in the pandemic period is effective) where from the total number of students, namely 54 people who have participated in this lecture activity, there are 79% all students have stated that this combination of learning can work effectively, especially during the covid-19 pandemic through research questionnaires given after students take statistics lectures